Educação, saberes psicológicos e morte voluntária: fundamentos para a compreensão da morte de si no Brasil colonial - Berenchtein Netto, Nilson (2012)
This research is a historical investigation, of bibliographical matrix, which aims to contribute to the building of a history of suicide in Brazil, from the role played by the education in relation to this phenomenon. The studied period circumscribes to that in which such lands were a Portuguese colony. The colonial period was structured under the slavery and has as main form of education that one promoted by the religious orders, especially the Society of Jesus (until 1759, when the Marquis of Pombal drove them out). We take education here in its broad sense, not restricted to the formal aspect. Such religious education was intended to control the life and the death of slaves. It is necessary to clearly understand that both, the Indians and Africans who were enslaved,had cultural and religious traditions very different from European, which made connect in different ways with death. Thus, compared to the excesses committed by settlers and the fact that these slaves commonly dying from overwork to which they were exposed, it became a common occurrence among these enslaved workers give themselves up voluntarily to death, to escape to the destiny of a short life, full of sufferings, and to undermine the slave masters or to escape punishment or separation of family and friends. Faced with this situation, the Catholic Church had a vital role, to inculcate in these individuals (mostly slaves, but also in the settlers) the guilt and the fear related to the voluntary death, a fact which allowed a strong entrance of the church in the control of the colony and fiercer exploitation by masters to their slaves, because each one shall bear his cross. In general, these lessons were transmitted through the sermons and prayers (mainly funeral and Lenten) uttered in public by the priests, but also in other types of situations, like for sermons printed in Portugal and circulated in the the colony or during the confessions. The Treatises of Moral Theology used in the formation of priests sometimes also devoted several pages to the issue of voluntary death and the way in which should the religious deal with and it and with those who search of it or conquer it. All items shown here, more extensive and detailed are presented and analyzed in this. The documental sources are the mentioned sermons and treatises, as well as texts of that period that could contribute to the contextualization of the phenomenon in the studied time and/or in the preceding history aiding in it s understanding. The documents are analyzed from a Marxist perspective in the History of Psychology and of the Cultural Historical Psychology